التشريعات المالية والمصرفية وانعكاساتها على برنامج الإصلاح الاقتصادي في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إنَّ طرح مشروع الإصلاح الاقتصادي لاقتصاد ما ينطوي على دلالة ضمنيَّة وعلنية تقول إنَّ هذا الاقتصاد كان يعمل وفقاً لمعايير وسياسات اقتصادية وقوانين وتشريعات تلبِّي الشروط المطلوبة لتحقيق الأهداف، ومن ثمَّ ونتيجة العولمة الاقتصادية أصبح هذا الاقتصاد ببنيته وقوانينه وتشريعاته عبئاً يحول دون تمكين المجتمع من التطوُّر والتقدُّم، لذلك تظهر أولوية الإصلاح الاقتصادي لمواجهة التحدِّيات الداخلية والخارجية، ومن الخطوات الأساسية الواجب أن يشملها برنامج الإصلاح الاقتصادي إصلاح القوانين والأنظمة وسن تشريعات جديدة، وانطلاقاً من ذلك ركَّز البحث على انعكاسات التشريعات المالية والمصرفية في سورية على برنامج الإصلاح الاقتصادي، حيث تمَّ التطرُّق إلى قانون المصارف وقانون الاستثمار وتعديلاته بالإضافة إلى قانون هيئة سوق الأوراق المالية، مع بيان أثر هذه القوانين وانعكاساتها على برنامج الإصلاح الاقتصادي في سورية، حيث تمَّ التوصُّل إلى مجموعة من الاستنتاجات منها: أنَّ تحديث التشريعات المالية والمصرفية يساعد على نجاح برنامج الإصلاح الاقتصادي في سورية، وفي نهاية البحث تمَّ التقدُّم بمجموعة من التوصيات منها: متابعة إصدار التشريعات المالية والمصرفية والاستفادة منها بالشكل الأمثل في نجاح برنامج الإصلاح الاقتصادي. Putting forward the project of economic reform for an economy includes an implicit and explicit idea implies that this economy was working according to economic standards and procedures, and laws and legislations that satisfy the required conditions to meet these  objectives. Then, as a result of economic globalization, this economy, with its structure, laws and legislations, became an obstacle that hinders the society development and progress. For these reasons the economic reform became a priority to face the internal and external challenges. The basic steps of economic reform include reforming laws and legislations, and putting new legislations. From these reasons, the research focuses on the effects of financial and banking legislations in Syria on the economic reform program. The banking regulation and investment law and its amendment in addition to the law of money market were mentioned, and the effect of these laws on the economic reform programs were shown, and we concluded to some conclusions such as: modernization of financial and banking legislations helps the success of Syrian economic reform programs. Finally, some recommendations were put forward, such as: ongoing issuing of financial and banking legislations and benefiting of them in the best way in the success of economic reform programs.